Economic Inequality: History, Case Studies and Policies - YOLUSEVER, ARAS (Türkiye Ekonomi Kurumu Vakfı, 2025)
The article delves into the intricate and long-standing issue of economic inequality, examining its historical origins, current manifestations, and potential policy solutions. It traces the evolution of inequality from ancient civilizations through feudal and industrial eras to modern capitalism, highlighting how historical social structures and economic systems have entrenched disparities in wealth and income. Case studies from Latin America, the post-Soviet states, and the United States illustrate the persistence and variation of inequality across different regions. The article also evaluates various policy responses aimed at addressing inequality, including progressive taxation, universal basic income (UBI), public investment in education and healthcare, and labor market reforms. While progressive taxation and public investments have effectively reduced inequality in some contexts, UBI remains a contested solution, with mixed results from pilot programs. The article argues for a comprehensive, multi-faceted approach that includes redistributive measures and structural reforms to promote a more equitable global economy.
İktisadi Eşitsizlik: Tarihi, Vaka Analizleri ve Politikalar
Keywords: Economic Inequality; History of Inequality; Tackling Inequality